1998
DOI: 10.1046/j.1365-2826.1998.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Receptor Gene Expression and Foetal Adipose Tissue

Abstract: We have investigated the effects of increasing gestational age, maternal undernutrition or restricted placental growth on prolactin receptor (PRLR) gene expression in perirenal adipose tissue collected from foetal sheep during late gestation (term = 147 d +/- 3 d of gestation). Foetal nutrient supply was reduced by either restriction of placental growth following removal of endometrial caruncles before mating or by reducing maternal feed intake by 50% from 115 d of gestation. Total RNA was extracted from adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 27 publications
2
47
1
Order By: Relevance
“…Increase in plasma prolactin (Houghton et al 1995) and prolactin receptor abundance (Symonds et al 1998) that may directly stimulate further expression of UCP1.…”
Section: Ontogeny Of Fetal Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Increase in plasma prolactin (Houghton et al 1995) and prolactin receptor abundance (Symonds et al 1998) that may directly stimulate further expression of UCP1.…”
Section: Ontogeny Of Fetal Adipose Tissuementioning
confidence: 99%
“…Reduced maternal nutrition in late gestation results in smaller fat depots with less UCP1 (Symonds et al 1998, Budge et al 2001, in conjunction with lower fetal plasma glucose and insulin, but has no effect of fetal leptin or prolactin receptor mRNA abundance (Symonds et al 1998, Yuen et al 2002. After birth, however, there appears to be a compensatory increase in VDAC abundance in nutrient-restricted offspring (Budge et al 2003) that is maintained up to at least 1 month of age (Mostyn et al 2003b).…”
Section: Nutritional Regulation Of Fetal Adipose Tissue Depositionmentioning
confidence: 99%
“…Although it is speculated that the short form of the PRL-R plays a role in such functions as reproduction and lactation in the ewe (Cassy et al 1998, Symonds et al 1998) and the rat (Telleria et al 1997, Feng et al 1998, no studies done to date have found a specific role for the short form of the receptor in the bovine. However, the present study identifies shifts in short form that occur in the same trend as the long form of the receptor, potentially indicating a role for the short form PRL-R in the bovine.…”
Section: Figurementioning
confidence: 99%
“…Both mRNA and protein for the PRLRs are highly abundant in fetal and neonatal brown adipose tissue (Symonds et al 1998, Bispham et al 1999. Growth of fetal fat occurs primarily over the second half of gestation when there is a marked rise in abundance of PRLR mRNA (Symonds et al 1998) preceding the rise in the abundance of the brown adipose tissue-specific mitochondrial protein, uncoupling protein (UCP)1 (Clarke et al 1997a) immediately after birth. Rapid activation of UCP1 in the newborn is critical in preventing hypothermia (Clarke et al 1997c).…”
Section: Introductionmentioning
confidence: 99%